(untitled) (Historia, 2021)
Schalk Pienaar, editor of the Sunday newspaper Die Beeld (1965-1970) and Beeld (1974), was a loyal, but critical member of the National Party. He believed that the survival of Afrikanerdom could only be ensured if it was based on justice for all South Africans and urged introspection about the morality of apartheid. His journalism encouraged reforms to the apartheid system, and did much to expose hypocrisy and deceit in the Afrikaner establishment. Apart from playing a leading role in making the Afrikaans press more independent and critical of the National Party, he also paved the way for the reforms of P.W. Botha and F.W. de Klerk.